Study of the Psychosocial Aspects of Epileptic Patient Attending the Middle Euphrates Neurological Sciences Center in AL-Najaf AL-Ashraf Province in Iraq - Salma KJ (Journal of Global Pharma Technology, 2018)
The findings of the present study indicated that the overall domains have an effect on patients with epilepsy among those domains social isolation which was the highest. Objectives: are to identify the demographic characteristics of the sample, also find out the impact of the epilepsy on patient psychosocial aspects, and Find out the relationship between the demographic characteristics of the patient and the impact of the epilepsy. Methodology: A descriptive Cross-sectional study was conducted on a non probability (purposive sampling) which consists of (100) patients with epilepsy who attending the Middle Euphrates Neurological Sciences Center in AL-Najaf AL-Ashraf Province, from September 16th 2016 to October 20th 2017.Results: The results of the study found that majority of participants are males and aged between (20-30) years old, most of them are married, high percentage of the sample was illiterate and regarding sample monthly income, it was found that patients were satisfied; age disease of onset found to be at (21-more) years old,  the majority them were non-smokers, the pathology of epilepsy is idiopathic more than symptomatic in clinical data. Finally there was no significant relationship between the overall patient’s psychosocial aspects and their clinical data also demographic data. Conclusion: The study concludes that social isolation is one of the psychosocial aspects that scored severs effect in many of the items, no significant relationship was found between the overall patient psychosocial aspects and the family and social support. Recommendations: Patients can be given more chances to share the health care providers with their experiences and all the issues related to the attack. It's better to provide the patients with an identification card clarifying some information about the particular patient.Keywords: Psychosocial aspects, Stigma, Epilepsy, Pathology of epilepsy.